International Strategy Configuration - Doina I. POPESCU (Revista de Management Comparat International)
The paper presents four international strategy configurations, namely, emphasize on local responsiveness, emphasize on global efficiencies with some local advantages, emphasize on global efficiencies, and seeking to exploit local advantages and global efficiencies. Also, the paper presents the peculiarities of multinational companies’ structure and design. Within the paper there are examples in order to illustrate the tradeoffs between local responsiveness and global efficiency and, also, examples that present the differences between organization structures in Japan and in the West. The paper underline the importance of formulation and implementation of international strategy in order to centralize/decentralized the value - chain activities.